2015
DOI: 10.1007/s40822-015-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there a low-risk anomaly across countries?

Abstract: The aim of this paper is to examine the parallels between the countrylevel and the stock-level low-risk anomalies. The inter-market variation in returns do not follow the intra-market patterns. Country-level returns are positively related to standard deviation, value at risk, and idiosyncratic volatility, although the effect is largely explained by cross-national value, size and momentum effects. The riskreturn relationship seems to be stronger in the cases idiosyncratic risk and is almost non-existent in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…In this case, higher volatility does not translate to positive implications for investors. This may explain why no low risk anomaly is observable at the index level (Zaremba, 2015c). Note: The Low to High columns refer to portfolios formed on past skewness.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, higher volatility does not translate to positive implications for investors. This may explain why no low risk anomaly is observable at the index level (Zaremba, 2015c). Note: The Low to High columns refer to portfolios formed on past skewness.…”
Section: Resultsmentioning
confidence: 99%
“…Chua et al [13] studies found that the expected stock returns are positively related to the idiosyncratic volatility. A sizable number of studies by Jiang and Lee [32], Malkiel and Xu [6], Drew et al [33], Huang et al [34] and Zaremba [35] also found positive relationship between expected returns and idiosyncratic volatility. Similarly, other set of studies by Ang et al [9,10], Guo and Savickas [11], Frieder and Jiang [12], Chua et al [13] and Peterson and Smedeman [36] found that idiosyncratic volatility is negatively related to the expect stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hou and Loh (2016) argued that existing literature provided explanations that could only explain less than 10% of the idiosyncratic volatility. Zaremba (2016) also studied the parallels between the country-level and the stock-level low-risk anomalies and found that country-level returns were positively related to standard deviation, value at risk, and idiosyncratic volatility. Saengchote (2017) confirmed that the abnormal returns associated with investment in low-beta stocks were significant and robust in Thai stock market.…”
Section: Introductionmentioning
confidence: 99%